20대 성인의 음성사용 시간에 따른 음성변화 연구 - 박현정(Hyun Jung Park); 이무경(Moo Kyung Lee); 권도하(Do Ha Kwon) (언어치료연구, 2010)
본 연구는 20대 성인 14명(남성 4명, 여성 10명)을 대상으로 음성사용 시간에 따른 음성변화 특징과 음성휴식시간에 따른 음성회복 특징을 음성사용 시간별로 음향학적 파라미터(F0, jitter, shimmer, NHR)를 측정하여 그 값에 차이가 있는가를 알아보았다. 피험자들은 읽기과업을 통한 120분의 음성사용 후 60분의 음성휴식을 취하였다. 20분 간격으로 MDVP를 통해 측정된 음향학적 파라미터들을 비교하여 음성변화 특징을 살펴보았으며, Person상관분석을 통해 음성변화시간과 음성회복시간과의 관련성을 알아보았다. 연구 결과, 전체 피험자 중 12명(85.7%)은 음질의 변화가 나타났으며, 2명(14.3%)은 음성사용 120분 동안 음질의 변화가 전혀 나타나지 않았다. 음성사용 시간에 따른 평균음성변화에서 음성사용 40분 후 전체피험자의 50%(7명)에서 음질에 변화를 보였으며, 80분 후 85.7%(12명)에서 음질변화가 나타났다. 그리고 jitter, shimmer, NHR은 60분 후 모두 정상범주에서 벗어났으며, 80분 후에 음질 변화가 최대로 나타났다. 음성 회복은 음성휴식 20분 후 25%, 40분 후 58.3%, 60분 후 75%의 피험자가 음질이 정상 범주로 회복되었다. 음성변화 시작시간과 음성회복 시간과의 관계는 유의한 음의 상관관계를 보여 음성변화가 일찍 시작된 피험자일수록 음성회복시간이 긴 것으로 나타났다(r=-.789, p<.01). This study measured acoustic parameters (F0, jitter, shimmer, NHR) by voice use time to investigate voice-change characteristic according to voice use time and the voice-recovery characteristics according to voice rest time. Fourteen adults (4 men, 10 women) in their 20s participated in the study which examined potential differences in their value. Subjects rested their voices for 60 minutes after having used their voices for 120 minutes through a reading task. Measured acoustic parameters were compared through MDVP at intervals of 20 minutes. Voice-change characteristics were then analyzed. Relationshipd between voice-change time and voice-recovery time were measured through Pearson correlation analysis. As a result of research, among whole subjects, 12 people (85.7%) were indicated to have a change in quality of voice. Two people (14.3%) were showed no change in voice quality after 120 minutes of use. In the voice change according to voice-use time, 50% of all subjects (7 people) showed a change in quality of voice after 40 minutes of use. After 80 minutes, 85.7% of subjects (12 people) indicated a change in quality of voice. And, jitter, shimmer, and NHR escaped all from the normal category after 60 minutes. After 80 minutes, the change in quality of voice was shown to be the highest. As for voice recovery, voice quality was recovered to normal levels in 25% of subjects after 20 minutes of voice rest, 58.3% after 40 minutes, and 75% after 60 minutes. The relationship between voice-change beginning time and voice-recovery time showed significantly negative correlation, thereby having been indicated that the subjects with the earlier beginning of voice change leads to the longer voice-recovery time (r=-.789, p<.01). KCI Citation Count: 0